PUBLIC OPINION ON NATIONAL HEALTH WELFARE SCHEMES WITH SPECIAL REFERENCE TO CHENNAI - A, Harshini; B, Sreeya (International Journal of Psychosocial Rehabilitation, 2020)
Health is a state in which disease and infirmity are absent. A state characterized by social, mental, physical well being. Only if health is proper and secured the country can develop as a whole. To create the well being of our nation, our nation has several health welfare schemes which were proposed by our leaders and representatives. The objectives of this research is to analyze the association between the sectors of health and the age and to examine the mean scores of agree ability towards factors for welfare schemes among the income groups. This research followed descriptive research method and convenient sampling method is used to collect the samples. The sample size is 1540. The dependent variables are health welfare schemes, health improvements, financial aid, food, employment, Medical assistance. The statistics used are Independent sample t test, chi square and ANOVA. It shows that the benefits of health welfare schemes depend on the gender of the respondents. It shows that the sectors of health are not depended on the age of respondents. So it can be concluded that the respondents are aware and give more importance on government schemes.